Carbon taxation in Europe - A. V. Korytin; N. S. Kostrykina; T. A. Malinina (Правоприменение, 2024)
The subject of the study is the carbon tax legislations of European countries.The purpose of the article is to identify the general consistent patterns of carbon taxation in a number of European countries: the United Kingdom, the Netherlands, Norway, France, Sweden and Switzerland.The methodology of the research includes the analysis of the provisions of the carbon taxing legislation of these countries.The main results, scope of application. The analysis shows that the structure of the carbon tax in European countries has differences, but the predominant form of taxation is an excise tax on fuel. In Sweden and Switzerland the excise rate is in direct proportion to the carbon content of the fuel, however in the UK, Norway and France excise rates are set more voluntary. Each country countries grant exemptions for specific fuel uses and industries that they deem essential to protect from the exceeding tax burden. In the Netherlands, Norway and France, carbon/energy taxation is applied in addition to the emissions trading system. In all these countries, this is motivated by the evaluation of the latter as insufficient to attain the objectives of diminishing CO2 emissions. Based on the experience of these countries, there is no prevalent model for the arrangement of carbon / energy taxation. For instance, France imposes an energy tax as an excise tax, that is, a consumption tax. The UK levies excise taxes on the consumption of natural gas, LNG, coal and electricity, correlated to the amount of energy contained in these fuel products. Norway applies both an excise and an indirect output tax in the oil sector.  In the Netherlands, a carbon tax is levied on actual CO2 emissions (as far as they are accounted for under the EU ETS), but this tax only applies to ETS participants and only if the ETS prices are below the established level. Despite the high tax rates (up to 120 euros per ton of CO2 in Sweden and Switzerland), the significance of the carbon tax for the economies of the considered countries is low due to both low energy consumption and the high proportion of carbon-neutral energy sources such as hydroelectric, nuclear and biofuel.Conclusions. An analysis of the provisions of the carbon taxing legislations of various European countries revealed that these countries adopt such carbon tax schemes that optimize their administrative feasibility, public acceptability, and economic impact mitigation for vital sectors. At the same time, in the majority of countries, the carbon tax is implemented as an excise tax on fuel.